Kidney outcomes associated with SGLT2 inhibitors compared to other glucose-lowering drugs: a real-world study from China - Xiao, Xiang; Ji, Shuming; Zheng, Tao; Wang, Tianzhu; Jiang, Dapeng; Liu, Fang (Frontiers in Pharmacology, 2024)
This study aimed to investigate the association between the utilization of Sodiumdependent glucose cotransporters inhibitors (SGLT2i) in real-world settings and kidney outcomes in patients with type 2 diabetes (T2D) and chronic kidney disease (CKD) in mainland China.In a retrospective analysis of electronic medical records from West China Hospital of Sichuan University, patients with T2D and CKD were included. Patients were divided into two groups, those initiating treatment with SGLT2i and those receiving other glucose-lowering drugs (oGLDs). The primary focus lies in examining the impact of SGLT2i on the decline slope of eGFR and major kidney events in these patients.We enrolled 944 patients diagnosed with both T2D and CKD. Out of these, 605 patients were prescribed SGLT2i, while the remaining 339 patients received oGLDs.The median follow-up duration were 16.8 months and 20.6 months, respectively.Throughout the follow-up period, we observed a significant decrease in the rate of eGFR decline in patients using SGLT2i (4.94 ml/min/1.73m 2 per year reduction compared to oGLDs, 95% CI: 4.73-5.15). A total of 101 kidney composite endpoint events occurred, with 31 events in the SGLT2i group and 70 events in the oGLDs group.The use of SGLT2i was associated with a 65% decrease in the risk of kidney composite endpoint events (hazard ratio 0.35, 95% CI 0.19-0.63).In clinical practice, SGLT2i have shown favorable effects on kidney prognosis in patients with T2D and CKD in mainland China. These effects remain consistent across patients with varying risks of CKD progression.